Reconstructions of Gender and Information Technology Women Doing IT for Themselves - Corneliussen, Hilde G.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
This open access book explores what makes women decide to pursue a career in male-dominated fields such as information technology (IT). It reveals how women experience gendered stereotypes but also how they bypass, negotiate, and challenge such stereotypes, reconstructing gender-technology relations in the process. Using the example of Norway to illuminate this challenge in Western countries, the book includes a discussion of the (3z(Bgender equality paradox(3y(B, where gender equality exists in parallel with gender segregation in fields such as IT. The discussion illustrates how the norm of gender equality in some cases hinders rather than promotes efforts to increase women$1 (Bs participation in technology-related roles.s
1. Women Fighting Gender Stereotypes in a Gender Egalitarian Culture -- 2. The Unsolved Mystery of the Gender Imbalance in IT -- 3. Women$1 (Bs Chronological Pathways to IT Education -- 4. Girl Power: Reconfiguring the Gendered Space of IT -- 5. Girls Don$1 (Bt Walk Alone: Supporters$1 (BInvestment in Welcoming Girls and Women into Fields of IT -- 6. Gender Patterns, Equality Paradoxes, and Lessons for an Inclusive Digital Future.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Science -- Social aspects; Sex; Industrial sociology; Technology -- Sociological aspects; Information technology; Science and Technology Studies; Gender Studies; Sociology of Work; Information and Communication Technologies (ICT).; Science, Technology and Society